SWEEP SINE WAVE BASED SHM FOR SHORT COMPOSITE TUBES - (:unkn) unknown (INT INST INFORMATICS & SYSTEMICS, 2010)
Composite tubes have been widely used for building the structures of the unmanned aerial vehicles (UAV). Monitoring the integrity of their structures would improve the safety and reliability of small UAVs. In this study, sweep sine wave was used for excitation of the carbon fiber tubes of a small four rotor helicopter. The piezoelectric elements attached to the tube acted as actuator and sensor. The actuator created the Lamb waves on the surface of the structure. The experimental data was collected by using a free tube and after a clamp was attached to the different locations of the tube. The S transforms of the sensory signals were used for analysis. Backpropagation type artificial neural networks were used for classification.
Keywords: Structure Health Monitoring; Sweep Sine Wave; S Transformation